Varsity blues - Laiter, Tova.; Tollin, Michael; Robbins, Brian, 1963-; Iliff, W. Peter; Van der Beek, James, 1977-; Voight, Jon, 1938-; Walker, Paul, 1973-2013; Lester, Ron.; Caan, Scott, 1976-; Isham, Mark.; Paramount Pictures Corporation (1914-1927); MTV Films (Firm); et al. (Hollywood, Calif. : Paramount Pictures, 1999)
A backup quarterback for the high school football team must confront the pressures and temptations of being a sports star, including conflicts with his coach and his girlfriend, when the starting quarterback is injured.
Originally produced as a motion picture in 1999.
Special features: theatrical trailer.
Music, Mark Isham.
James van der Beek, Jon Voight, Paul Walker, Ron Lester, Scott Caan.
MPAA rating: Rated R; for strong language throughout, sexuality and nudity, and some substance abuse.
DVD; English track: Dolby digital 5.1.
Keywords: Football players -- Drama; School sports -- Drama; Sex -- Drama; Drug abuse -- Drama; Sports films; Feature films; Films for the hearing impaired